A newly identified mouse hypothalamic area having bidirectional neural connections with the lateral septum: the perifornical area of the anterior hypothalamus rich in chondroitin sulfate proteoglycans. (19th August 2015) - Horii‐Hayashi, Noriko; Sasagawa, Takayo; Hashimoto, Takashi; Kaneko, Takeshi; Takeuchi, Kosei; Nishi, Mayumi; Barbas, Helen
Abstract While previous studies and brain atlases divide the hypothalamus into many nuclei and areas, uncharacterised regions remain. Here, we report a new region in the mouse anterior hypothalamus (AH), a triangular‐shaped perifornical area of the anterior hypothalamus (PeFAH) between the paraventricular hypothalamic nucleus and fornix, that abundantly expresses chondroitin sulfate proteoglycans (CSPGs). The PeFAH strongly stained with markers for chondroitin sulfate/CSPGs such as Wisteria floribunda agglutinin and antibodies against aggrecan and chondroitin 6 sulfate. Nissl‐stained sections of the PeFAH clearly distinguished it as a region of comparatively low density compared to neighboring regions, the paraventricular nucleus and central division of the anterior hypothalamic area. Immunohistochemical and DNA microarray analyses suggested that PeFAH contains sparsely distributed calretinin‐positive neurons and a compact cluster of enkephalinergic neurons. Neuronal tract tracing revealed that both enkephalin‐ and calretinin‐positive neurons project to the lateral septum (LS), while the PeFAH receives input from calbindin‐positive LS neurons. These results suggest bidirectional connections between the PeFAH and LS. Considering neuronal subtype and projection, part of PeFAH that includes a cluster of enkephalinergic neurons is similar to the rat perifornical nucleus and guinea pig magnocellular dorsal nucleus. Finally, we examined c‐Fos expression after several types of stimuli and found that PeFAH neuronal activity was increased by psychological but not homeostatic stressors. These findings suggest that the PeFAH is a source of enkephalin peptides in the LS and indicate that bidirectional neural connections between these regions may participate in controlling responses to psychological stressors.